2017
DOI: 10.1016/j.neuropsychologia.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Early use of phonological codes in deaf readers: An ERP study

Abstract: Previous studies suggest that deaf readers use phonological information of words when it is explicitly demanded by the task itself. However, whether phonological encoding is automatic remains controversial. The present experiment examined whether adult congenitally deaf readers show evidence of automatic use of phonological information during visual word recognition. In an ERP masked priming lexical decision experiment, deaf participants responded to target words preceded by a pseudohomophone (koral - CORAL) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 81 publications
2
34
0
Order By: Relevance
“…Based on a masked phonological priming paradigm, Gutierrez-Sigut et al (2018) reported that deaf individuals showed faster word identification times in the pseudo-homophone than in the control condition. Similar results were reported in a study using both behavioural and ERP measures (Gutierrez-Sigut et al, 2017) and in a study on English children by Blythe et al (2018). Transler and Reitsma (2005) found that pseudo-homophony effects were present but smaller in deaf individuals than in hearing controls.…”
Section: Introductionsupporting
confidence: 85%
“…Based on a masked phonological priming paradigm, Gutierrez-Sigut et al (2018) reported that deaf individuals showed faster word identification times in the pseudo-homophone than in the control condition. Similar results were reported in a study using both behavioural and ERP measures (Gutierrez-Sigut et al, 2017) and in a study on English children by Blythe et al (2018). Transler and Reitsma (2005) found that pseudo-homophony effects were present but smaller in deaf individuals than in hearing controls.…”
Section: Introductionsupporting
confidence: 85%
“…Specifically, the size of the N400 effect was strongly correlated with reading ability for deaf but not hearing individuals. A similar finding was reported by Gutierrez-Sigut et al (2017) for the N400 pseudohomophone priming effect with single words; that is, the size of the N400 effect correlated with reading ability for deaf but not hearing participants. In contrast, the size of the P600 response to syntactic violations was related to reading ability for the hearing but not the deaf participants.…”
Section: <1> Sentence Readingsupporting
confidence: 85%
“…Pseudohomophones are nonwords that sound like real words if pronounced (e.g., werk, brane). Gutierrez-Sigut et al (2017) found evidence for pseudohomophone priming in both their behavioral and ERP results. Deaf readers made faster lexical decisions when the target word was preceded by a pseudohomophone prime (koral -CORAL) than an orthographically-related nonword prime (toral -CORAL), and the N250 amplitude was reduced (indicating priming) for the pseudohomophone compared to the orthographic control condition.…”
Section: <3> the N250 Response And Sublexical Processesmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, in our experimental procedures, a blank screen was presented between the prime and target, which could make the prime stimulus more salient, and therefore might increase the possibility that participants could process the prime consciously. Note that a recent ERP study also inserted a blank period between prime and target in order to maximize the size of the priming effects (Jiang, 1999 ; Gutierrez-Sigut et al, 2017 ). An interesting goal for future research is to carefully examine how differences in priming techniques might modulate the magnitude of priming effects.…”
Section: Discussionmentioning
confidence: 99%